TEACHER'S INFLUENCE ON IMPROVING THE QUALITY OF TEACHING - LEARNING FOR PRIMARY SCHOOL STUDENTS - ATTACHED TO THE IFP IN PEMBA CITY - Tiago, Lázaro Ernesto (Seven Editora, 2025)
In Mozambique, education is a right and duty of citizens and aims to provide everyone with equal opportunities to access all levels of education. The teacher's job is to teach children, youth, and adults and ensure the quality of the teaching-learning process, promoting their intellectual and social development. In this context, teachers are called upon to be present throughout the educational process, ensuring quality learning and plausible outcomes. This reflection aims to understand the influence of teachers on the quality of the teaching-learning process, using a qualitative approach. The research found a new positive attitude among students, demonstrating interest in classes and taking good care of their books and teaching materials, under their teachers' guidance. Recently, students have shown greater concern for the teaching-learning process, even without parental guidance to motivate them to participate in learning. Teachers address problems affecting teachers, students, school infrastructure, and the school community through self-assessment to ensure improved performance. Slow-learning children should undergo a qualitative assessment, with the assessment elements including student motivation, attendance, punctuality, and classroom participation.DOI: https://doi.org/10.56238/sevened2025.030-087